TUCO Secures Home For Aged Calypsonians - Joseph, Terry (Express)
Trinbago Unified Calypsonians Organisation (TUCO) has handed over a property worth $80,000 situated at 7 North Bank Road in Centeno. The facility will be used as a geriatric home for aged calypsonians.
Keywords: Calypso musicians -- Trinidad and Tobago; Older people -- Trinidad and Tobago; Homes for the Aged -- Trinidad and Tobago